FIGURATIVE LANGUAGE USED IN ONE DIRECTION’S ALBUM ENTITLED UP ALL NIGHT - Fitria, Tira Nur (Elite : English and Literature Journal, 2018)
Abstract The aims of this study are to know the types of figurative languages and to know the most dominant figurative language used in lyrics One Direction’s album song entitled Up All Night. The research is qualitative descriptive to describe the analysis factually, accurately and systematically. The data in this research include the phrases or the sentences which found in lyric album song entitled “Up All Night” by One Direction. The data source of this study is album song entitled “Up All Night” by One Direction. Based on research finding, it can be found that there are some figurative languages in One Direction’s album “Up All Night”. There were 13 songs in this album, they are: 1) Everything About You, 2) Gotta Be You, 3) I Want, 4) I Wish, 5) More Than This, 6) One Thing, 7) Same Mistakes, 8) Save You Tonight, 9) Stole My Heart, 10) Taken, 11) Tell Me a Lie, 12) Up All Night and 13) What Makes You Beautiful. Based on the result of this research, it is found six types of figurative language in One Direction’s album entitled “Up All Night”, that are repetition, parallelism, personification, metaphor, simile and hyperbole. While, the most dominant type of figurative language used is repetition, there are 50 lyrics that contain repetition both anaphora and epiphora. Key Words: figurative language, song, album.